Eritrean teachers' challenges of their enthusiasm for digital competency and its impact on teaching performance - Samson Kifletsion Elias; Irene Musengamana; Amare Teclemicael Mebrahtu (Springer, 2023)
Abstract The interaction of education and digital technology today is one of the key characteristics of development. Many industrialized nations place a high value on digital learning practices and have created several national strategic plans to encourage and support the use of digital practices in education. In its reform and development of education, Eritrea has also made the strategic decision to assist educational modernization using a clear digital policy. Eritrea has made significant advancements in the creation of technology infrastructure, the use of digital resources, innovative teaching methods, and technology-supported educational management to date. However, there are still issues with execution brought on by teachers' preparation, public spending, and human resources. The study collected useful information from n = 141 active student-teachers participating in post-graduate diploma (PGD) practice at Asmara College of Education utilizing both qualitative and quantitative research methodologies. Results have been reported using special and original quotes together with both descriptive and inferential statistics. The study's conclusions show that teachers' enthusiasm for using ICT in the classroom will have a favorable effect on their ability to teach, assisting them in becoming aware of the modernized world and adjusting to its expectations. The knowledge of the teachers has a big impact on digital activities. Additionally, the research has revealed that Eritrean school instructors have little knowledge of using ICT in teaching and learning to improve student performance. The perception of teachers' preparation for digital competency is positive, even though a noteworthy problem is being highlighted that prevents teaching and learning from succeeding. They have a very high and favorable opinion of how the use of technology has affected their ability to teach.